2019
DOI: 10.1021/acs.nanolett.9b02067
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Alignment of a Monolayer of Flat-on Free-Base Porphyrins on an Exfoliable Insulating Substrate

Abstract: Porphyrins are an extremely valuable class of molecules engaged in a variety of roles spanning from biology to optoelectronics. Manipulation of the chemical and physical properties of the inner cavity of porphyrins has been recognized as crucial for the exploitation of these systems in organic devices, particularly when porphyrins self-organize at the interface with a flat-on orientation of the macrocycle. Such an orientation has been mostly observed on metallic surfaces. Unfortunately, the physical-chemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…At this thickness, we demonstrated that H 2 TPP (inset Figure A) reaches maximum coverage of its wetting layer, constituted by flat-on molecules with a frozen configuration of their tautomeric form and arranged in a square lattice (Figure S1). ,, The height of the steps on the surface is within the range 0.3–0.5 nm, consistent with the spacing of elemental steps of the substrates ( d 110 = 3.10 Å for DKP:FA and d 0001 = 3.35 Å for HOPG) or the thickness of the wetting layer (4.5–5.5 Å). For a nominal thickness higher that 2.0 Å, 3D islands start nucleating and growing up to a height of 5–10 nm.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…At this thickness, we demonstrated that H 2 TPP (inset Figure A) reaches maximum coverage of its wetting layer, constituted by flat-on molecules with a frozen configuration of their tautomeric form and arranged in a square lattice (Figure S1). ,, The height of the steps on the surface is within the range 0.3–0.5 nm, consistent with the spacing of elemental steps of the substrates ( d 110 = 3.10 Å for DKP:FA and d 0001 = 3.35 Å for HOPG) or the thickness of the wetting layer (4.5–5.5 Å). For a nominal thickness higher that 2.0 Å, 3D islands start nucleating and growing up to a height of 5–10 nm.…”
Section: Resultssupporting
confidence: 71%
“…Flat-on arrangements of porphyrins are routinely obtained on metal substrates such as Au, Ag, Cu, and HOPG, but hardly on low interacting surfaces. Recently, we demonstrated the growth of a stable wetting layer of free-base tetraphenyl porphyrin (H 2 TPP; see inset of Figure ) in a flat-on configuration on an insulating substrate, constituted by the triclinic mixed crystal formed by 2,5-diketopiperazine (DKP) and fumaric acid (FA) in a 1:1 mole ratio (DKP:FA). , The difficulty of accomplishing this result lies in the absence in H 2 TPP of functional groups promoting strong interactions with the substrate and/or particular in-plane assemblies. , Under these conditions, the epitaxial match between substrate and overlayer was demonstrated to be the fundamental driving force enabling the controlled growth of the molecular monolayer. Here, we show by high-resolution atomic force microscopy (AFM) investigations that the flat-on arrangement is retained in crystalline domains of subsequent 3D structures and we disclose the presence of two other epitaxial molecular arrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are reasonably due to a 2D phase of the organic film, which represents a sort of wetting layer for the evolution of the crystals. [16,31] After a single exposure to hydrochloric vapors, the sample morphology is significantly different (see panel b): as expected, the 3D structures are transformed in organic molecules agglomerates. Considering that the intensity of the film optical spectrum is almost recovered after the first acid exposure (see Figure 5) while it is not the case for the morphology (see Figure 6), we deduce that SDR arises mainly from the 2D phase, in close agreement with the results acquired on porphyrin films.…”
Section: Optical Reflectivity Properties Of Thin Filmssupporting
confidence: 62%
“…It is also possible to observe false color changes on the substrate terraces. These are reasonably due to a 2D phase of the organic film, which represents a sort of wetting layer for the evolution of the crystals [16,31] . After a single exposure to hydrochloric vapors, the sample morphology is significantly different (see panel b ): as expected, the 3D structures are transformed in organic molecules agglomerates.…”
Section: Resultsmentioning
confidence: 62%